2020
DOI: 10.3847/1538-4357/ab8ad4
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Transfer Modeling of EC 53: An Episodically Accreting Class I Young Stellar Object

Abstract: In the episodic accretion scenario, a large fraction of the protostellar mass accretes during repeated and large bursts of accretion. Since outbursts on protostars are typically identified at specific wavelengths, interpreting these outbursts requires converting this change in flux to a change in total luminosity. The Class I young stellar object EC 53 in the Serpens Main cloud has undergone repeated increases in brightness at 850 μm that are likely caused by bursts of accretion. In this study, we perform two-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 86 publications
6
22
0
Order By: Relevance
“…(2020) empirically uncovered a submillimeter-to-protostellar luminosity exponential factor of ∼4, and confirmed that it matched well with radiative transfer expectations (Baek et al 2020). Thus, assuming that the protostellar luminosity is a reasonably linear proxy for protostellar accretion, it is appropriate to consider the importance of the variable mass accretion uncovered by these submillimeter observations.…”
Section: Variability As a Proxy For Episodic Mass Accretionsupporting
confidence: 58%
See 1 more Smart Citation
“…(2020) empirically uncovered a submillimeter-to-protostellar luminosity exponential factor of ∼4, and confirmed that it matched well with radiative transfer expectations (Baek et al 2020). Thus, assuming that the protostellar luminosity is a reasonably linear proxy for protostellar accretion, it is appropriate to consider the importance of the variable mass accretion uncovered by these submillimeter observations.…”
Section: Variability As a Proxy For Episodic Mass Accretionsupporting
confidence: 58%
“…Based on its bolometric temperature and spectral index, EC 53 is a Class I source (Evans et al 2009;Dunham et al 2015). However, the envelope contains ∼6 M e (Baek et al 2020), while the protostar and disk masses are only 0.3 M e and 0.07 M e , respectively (Lee et al 2020a), suggestive of a much younger evolutionary state. Periodic variability has been observed previously in the near-IR (Hodapp 1999;Hodapp et al 2012), MIR (Contreras Peña et al 2020), and the submillimeter (Mairs et al 2017b;Yoo et al 2017;Johnstone et al 2018).…”
Section: B2 Serpens Main Ec 53 (V371 Serp): Periodic Groupmentioning
confidence: 99%
“…Previously, disk accretion rates have been measured through the bolometric luminosity and/or molecular emission at large radii (>500 au). On the other hand, a detailed 2D model of a bursting Class I protostar can capture the current disk structure and infer the more accurate accretion rate during the burst (e.g., Baek et al 2020;Lee et al 2020). From the bolometric luminosity of TMC1A (L bol = 2.7 L , Kristensen et al 2012), the accretion rate is inferred to be ∼3 × 10 −7 M yr −1 .…”
Section: Accretion Processes In a Young Diskmentioning
confidence: 99%
“…Previously, disk accretion rates have been measured through the bolometric luminosity and/or molecular emission at large radii (> 500 au). On the other hand, a detailed 2D model of a bursting Class I protostar can capture the current disk structure and infer the more accurate accretion rate during the burst (e.g., Baek et al 2020;Lee et al 2020). From the bolometric luminosity of TMC1A (L bol = 2.7 L , Kristensen et al 2012), the accretion rate is inferred to be ∼ 3 × 10 −7 M yr −1 .…”
Section: Accretion Processes In a Young Diskmentioning
confidence: 99%